Simulacrum. New modes of Representation in the post-contemporary spectacle - Paz Gago, José María (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The massive incursion of audiovisual technologies, first analog and then digital, during the second half of the 20th century, modified the theatrical spectacle, invaded by projections and screens with a more or less artistically relevant functionality (Paz Gago 2006a and 2013). The irruption of much more advanced and sophisticated technologies such as virtual reality, already in the 21st century, is causing an even deeper metamorphosis of the spectacle. The central question is whether it will transform its very semiotic nature. Actors replaced by their virtual avatars, immersive projection scenographies, reception through sensory devices… colonize scenics shows that will be analyzed here. The transformation is so radical that, for the first time in twenty-five centuries, the end of the Representation mode is proposed, which would be replaced by the Simulation mode.
Keywords: Spectacle; Semiotics; Representation; Simulation